2019
DOI: 10.1001/jamanetworkopen.2019.12431
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Association Between Organ Availability and Presumed Consent in Solid Organ Transplant

Abstract: Key PointsQuestionWhat are the plausible implications of a presumed consent transplant policy for waiting list outcomes in the United States?FindingsIn this simulation study of 524 359 potential organ recipients in a decision analytical model, a presumed consent policy was estimated to be associated with a reduction in waiting list removals. This estimation translated to an increase in life-years gained for patients in this simulation.MeaningThis study suggests that implementation of a presumed consent policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
0
19
0
5
Order By: Relevance
“…Fourth, this study assesses the quality of OP policies by focusing only on their capacity to preserve and promote societal values. It does not address the question of the effectiveness of presumptive policies, which has been extensively explored elsewhere [ 28 , 29 ]. As health policies attempt to foster optimal results while minimally compromising people’s interest, future research that combines both approaches would be much welcomed.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, this study assesses the quality of OP policies by focusing only on their capacity to preserve and promote societal values. It does not address the question of the effectiveness of presumptive policies, which has been extensively explored elsewhere [ 28 , 29 ]. As health policies attempt to foster optimal results while minimally compromising people’s interest, future research that combines both approaches would be much welcomed.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent academic publications in this domain conclude that changes in donor numbers cannot be attributed to the organ donation system alone. [13][14][15][16][17] They contend that other factors at multiple health system and population levels require consideration.…”
Section: Overview Of Main Argumentsmentioning
confidence: 99%
“…To illustrate the potential impact of our findings, if we were to assume that everything held constant over time and we introduced our best-performing intervention (reciprocal altruism) throughout Ontario, we could expect roughly 225,000 additional new registrations annually. While quantifying the effect of increased registrations on the ultimate goal-lives saved or enhanced-is challenging (see, e.g., DeRoos et al 2019), research has shown that those who register their consent are significantly more likely to actually donate than those who have not (Christmas et al 2008). Specifically, the majority of registered individuals in Ontario who become eligible to donate are ultimately converted to donors (Toews and Caulfield 2016), and Ontario's Trillium Gift of Life Network (2020) advertises that one single donor may save up to eight lives and enhance as many as 75 more lives.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%